2015
DOI: 10.1590/1983-21252015v28n329rc
|View full text |Cite
|
Sign up to set email alerts
|

Fontes Alternativas De Pólen Utilizadas Pelo Bicudo-Do-Algodoeiro Em Duas Regiões Produtoras De Algodão Na Bahia

Abstract: RESUMO -O bicudo-do-algodoeiro (Anthonomus grandis Boheman) (Coleoptera: Curculionidae) é um dos principais fatores limitantes para a expansão da cultura do algodão. Ele apresenta diferentes aspectos biológicos e comportamentais que garantem seu sucesso na exploração do agroecossistema algodoeiro. O objetivo deste trabalho foi identificar os recursos alimentares utilizados pelo bicudo na safra e entressafra de cultivos de algodão localizados nos municípios de Iuiu e Correntina (BA) e em ambientes de Caatinga e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 14 publications
1
10
0
1
Order By: Relevance
“…At the end of the crop cycle, the adults search for alternative food sources and shelter in order to survive the fallow period. This mass egress, both during and after the harvesting procedures, has been reported in the state of São Paulo, in the Distrito Federal, and in the state of Bahia by Campanhola et al (1988), Ribeiro et al (2010), and Macêdo et al (2015), respectively, and has been confirmed in monitoring studies using traps baited with pheromone, carried out in cotton-producing areas in the state of Goiás (Lima Jr. et al, 2013).…”
Section: Resultssupporting
confidence: 73%
See 4 more Smart Citations
“…At the end of the crop cycle, the adults search for alternative food sources and shelter in order to survive the fallow period. This mass egress, both during and after the harvesting procedures, has been reported in the state of São Paulo, in the Distrito Federal, and in the state of Bahia by Campanhola et al (1988), Ribeiro et al (2010), and Macêdo et al (2015), respectively, and has been confirmed in monitoring studies using traps baited with pheromone, carried out in cotton-producing areas in the state of Goiás (Lima Jr. et al, 2013).…”
Section: Resultssupporting
confidence: 73%
“…However, the physiological reduction in reproduction does not keep boll weevils from moving and searching for food to survive until the cotton fields have been planted again and squares begin to form (Jones et al, 1992;Hardee et al, 1999;Showler & Abrigo, 2007;Ribeiro et al, 2010;Macêdo et al, 2015). In addition, these areas may possibly provide shelter for adult boll weevils to protect themselves against adverse conditions, such as low humidity and high temperatures, both typical of this region in the cotton fallow period.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations